Evolution of RXLR-Class Effectors in the Oomycete Plant Pathogen Phytophthora ramorum - Goss, Erica M.; Press, Caroline M.; Grünwald, Niklaus J. (PloS one, 2013)
Phytophthora plant pathogens contain many hundreds of effectors potentially involved in infection of host plants. Comparative genomic analyses have shown that these effectors evolve rapidly and have been subject to recent expansions. We examined the recent sequence evolution of RXLR-class effector gene families in the sudden oak death pathogen, P. ramorum. We found that P. ramorum RXLR effectors have taken multiple evolutionary paths, including loss or gain of repeated domains, recombination or gene conversion among paralogs, and selection on point mutations. Sequencing of homologs from two subfamilies in P. ramorum's closest known relatives revealed repeated gene duplication and divergence since speciation with P. lateralis. One family showed strong signatures of recombination while the other family has evolved primarily by point mutation. Comparison of a small number of the hundreds of RXLR-class effectors across three clonal lineages of P. ramorum shows striking divergence in alleles among lineages, suggesting the potential for functional differences between lineages. Our results suggest future avenues for examination of rapidly evolving effectors in P. ramorum, including investigation of the functional and coevolutionary significance of the patterns of sequence evolution that we observed.